Efetividade da tutela preventiva - Feriani Filho, Luis Arlindo (2016)
This paper aims to examine the boundaries, contours, and potential difficulties for achieving a fully-effective preventive custody. It is expected to demonstrate that contemporary society, mass, plural and surrounded by numerous relationships of all kinds can do nothing without a genuinely preventive protection and open to welcome and really protect the varied existing situations. Undeniably, the development of society has given rise to and develop a series of rights and guarantees that require the improvement of the procedural system so that they can indeed be preserved, particularly because they involve the maintenance of character eminently off-balance sheet nature of content and therefore call for a more active role by the judiciary for achieving effective preventive protection, since it is not consistent with the private and repressive model of jurisdiction. It happens that, due to the proximity of the conceptual structures of procedural law to the liberal state and, from that, the minimum intervention in individual freedoms, the clear separation of powers, the jurisdiction of concepts, action, procedural interest, especially, were strongly influenced so that the jurisdictional activity is based almost exclusively for remedial tutelage, creating some doctrines that must be overcome. The difficulties linked to the role given to the judiciary, the ordinariness of the procedures as a means of supposed equal treatment for all situations, an exhaustive presentation of evidence as the real truth discovery so are some of the elements which still are strongly present and end up represent real obstacle to protecting the threat to the right. Therefore, it examined some of the criteria and values brought by the doctrine in order to have procedural effectiveness, the importance and role of the state, justice and the process, including the call distributive justice so that, later, the particulars are facing the preventive custody and require different treatment and change the paradigms that to this day are present. In the end, it advocates the need for improvements to achieve the effectiveness of preventive care, which requires the construction of new paradigms and possible legislative adjustments